PERAN CITRA MEREK DALAM MENARIK MINAT KONSUMEN PADA PRODUK LOKAL: Menelaah Peran Citra Merek dalam Membentuk Niat Beli Konsumen terhadap Produk Lokal: Tinjauan Pustaka - Aida Aprilia; Moh. Mukhsin (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
This study aims to conceptually examine the role of brand image in shaping consumer purchase intention toward local products, as well as to identify its supporting factors. The method used is strictly library research with a descriptive-analytical approach, synthesizing various previous literature from published academic journals. The results of the literature synthesis indicate that purchase intention does not form in a vacuum but is triggered by functional advantages (product innovation, price perception, and digital promotion). Furthermore, this study confirms the theoretical position of brand image as the main mediator variable or